2003
DOI: 10.1038/sj.bmt.1704069
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, survival and risk factors for the development of veno-occlusive disease in pediatric hematopoietic stem cell transplant recipients

Abstract: Summary:The incidence, risk factors and mortality of veno-occlusive disease (VOD) were identified for 142 pediatric hematopoietic stem cell (HSC) transplant recipients with hematological malignancies (83), solid tumors (41) and nonmalignant diseases (18). This historical cohort of 142 HSC transplant patients, from January 1993 through June 2000, was assessed by chart review. Risk factors for the development of VOD and mortality were assessed by multiple logistic regression and Kaplan-Meier survival curves resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(93 citation statements)
references
References 32 publications
6
83
2
2
Order By: Relevance
“…BU is needed. On the other hand, we found that the addition of CY to BU was an additive risk factor for VOD, similar to the study by Barker et al 4 It has been proposed that BU might influence the metabolism of CY, causing an increase in toxic metabolites which are associated with VOD. 20,21 CY itself was also reported to be Table 5 Summary of risk factors for hepatic VOD in previous pediatric studies and the current study associated with VOD.…”
Section: Risk Factorssupporting
confidence: 75%
See 1 more Smart Citation
“…BU is needed. On the other hand, we found that the addition of CY to BU was an additive risk factor for VOD, similar to the study by Barker et al 4 It has been proposed that BU might influence the metabolism of CY, causing an increase in toxic metabolites which are associated with VOD. 20,21 CY itself was also reported to be Table 5 Summary of risk factors for hepatic VOD in previous pediatric studies and the current study associated with VOD.…”
Section: Risk Factorssupporting
confidence: 75%
“…1,2 The cause of hepatic VOD is not entirely clear but a number of risk factors have been reported. [3][4][5][6] While many cases of mild VOD resolve spontaneously without complications, moderate-to-severe VOD may result in significant morbidity or even mortality. The management of VOD is mainly supportive, including fluid restriction and diuretics to ameliorate fluid retention and cardio-respiratory support if necessary.…”
Section: Introductionmentioning
confidence: 99%
“…10,[12][13][14][15] Identifying the risk factors for HVOD should then enable us to reduce the usual incidence (20-30%) of this disease 5,7,11 and possibly also lower the 5-10% toxicity-related mortality. 11 Several risk factors for HVOD have already been described.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In pediatric series, it usually occurs during the first 4 weeks after AHSCT in up to 40% of patients. [4][5][6] Histologically, it is characterized by nonthrombotic occlusion of the centrilobular veins with necrosis of centrilobular hepatocytes. 6 The diagnosis is based on McDonald's clinical criteria.…”
Section: Introductionmentioning
confidence: 99%
“…7 Forced expiratory volume and forced vital capacity are the best tests to detect pulmonary abnormalities, both in symptomatic and in asymptomatic patients. 32, 43 Forced Table 1 Type and frequency in paediatric age of the most frequent early and late toxicities that occur after HSCT Euthyroid sick syndrome 13 Compensated or overt hypothyroidism (15-2.1) 14 Leydig cell failure (7) 15 Germ cell failure (after TBI 99) 16 Delayed menarche (after TBI 44) 15 Overt ovarian failure (after TBI 90) 16 Growth impairment Liver VOD (4.6-41) [17][18][19] Viral hepatitis (14-50), 20 iron overload (52) expiratory volume and forced vital capacity levels of less than 85% before transplant can predict pulmonary failure, and patients with pulmonary function test abnormalities should be carefully followed up, especially if they develop cGVHD.…”
Section: Risk Features For Cataractmentioning
confidence: 99%